Pengaruh Ukuran Partikel Tepung Kerabang Telur yang Diperlakukan dengan Asam Fosfat dalam Pakan terhadap Penampilan, Kualitas Telur dan Status Plasma Darah Ayam Petelur - , Galuh Adi Insani; , Prof. Dr. Ir. Tri Yuwanta, SU, DEA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aims was to study the effect of particle size of egg shell waste mash which was treated with different levels of phosphoric acid as a source of minerals in laying hen on performance, eggs quality, and levels of Ca and P blood plasm diets. Eggshell waste was collected from bakery, and was separated into three treatments (K0/control) eggs shell washed with hot water of 800 C